1999
DOI: 10.2307/3345830
|View full text |Cite
|
Sign up to set email alerts
|

Aural-Diagnostic and Prescriptive Skills of Preservice and Expert Instrumental Music Teachers

Abstract: This study is an investigation of the aural-diagnostic and prescriptive skills of preservice and expert instrumental music teachers. Specifically, the researcher sought to determine how the two groups compared with respect to evaluations for band performances of different music-difficulty and performance-quality levels. Subjects listened to an audiotape recording that comprised four types of performances: Difficult Music and Excellent Performance, Difficult Music and Average Performance, Moderate Music and Exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
36
1

Year Published

2004
2004
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 8 publications
(13 reference statements)
2
36
1
Order By: Relevance
“…Hoffren, 1964). There is some evidence showing that inexperienced music teachers are less able to diagnose performance problems concerning emotional expression than are expert teachers (Doerksen, 1999). The Feel-ME program could assist teachers in identifying weaknesses with re-spect to specific aspects of a performer's expressive strategy.…”
Section: Advantages Of the Feel-me Approachmentioning
confidence: 99%
“…Hoffren, 1964). There is some evidence showing that inexperienced music teachers are less able to diagnose performance problems concerning emotional expression than are expert teachers (Doerksen, 1999). The Feel-ME program could assist teachers in identifying weaknesses with re-spect to specific aspects of a performer's expressive strategy.…”
Section: Advantages Of the Feel-me Approachmentioning
confidence: 99%
“…This differs from findings of other researchers (Doerksen, 1999;Ekholm, 1997;Fiske, 1977). The investigators in the current study sought to evaluate junior high trumpet players, whereas most of the other studies involving individual performance were examinations of college-level performers (Bergee, 1993(Bergee, , 1997(Bergee, , 2003Ekholm, 1997;Fiske, 1977Fiske, , 1979Mills, 1987).…”
Section: Discussionmentioning
confidence: 71%
“…Experience in teaching may play an important role in the ability to evaluate music performance. In a study examining differences in preservice and expert teachers, Doerksen (1999) found that preservice teachers rated some "excellent" performances of band music lower in tone quality, intonation, articulation, and dynamics than did expert teachers. Average performances were rated similarly by both groups.…”
mentioning
confidence: 99%
“…The study suggests that innovation in teaching style and delivery should be an integral part of any assessment model when measuring conductor effectiveness. Doerksen (1999) studied the differences in aural-diagnostic and prescriptive skills used by preservice and expert instrumental music teachers. Prior research indicated that certain teaching characteristics were germane to specific disciplines.…”
mentioning
confidence: 99%
“…Doerksen (1999) noted that when considering prescriptive groupings, pre service teachers believed that nonverbal communication was more important while expert teachers placed greater importance on instruments/accessories. This may be an indication that expert teachers regularly use verbal explanations to correct musical problems.…”
mentioning
confidence: 99%